2022
DOI: 10.3389/fsufs.2022.888041
|View full text |Cite|
|
Sign up to set email alerts
|

Evaluation and Multivariate Analysis of Cowpea [Vigna unguiculata (L.) Walp] Germplasm for Selected Nutrients—Mining for Nutri-Dense Accessions

Abstract: A total of 120 highly diverse cowpea [Vigna unguiculata (L.) Walp] genotypes, including indigenous and exotic lines, were evaluated for different biochemical traits using AOAC official methods of analysis and other standard methods. The results exhibited wide variability in the content of proteins (ranging from 19.4 to 27.9%), starch (from 27.5 to 42.7 g 100 g−1), amylose (from 9.65 to 21.7 g 100 g−1), TDF (from 13.7 to 21.1 g 100 g−1), and TSS (from 1.30 to 8.73 g 100 g−1). The concentration of anti-nutrition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 51 publications
2
12
0
Order By: Relevance
“…Four hundred seventy-five accessions of cowpea consisting of indigenous and exotic collections were taken from MTS of National Gene Bank at ICAR-NBPGR, New Delhi, India, having high variability in seed morphology. Using Augmented Block Design accessions were grown in Issapur experimental farm, New Delhi, India, following standard agronomic practices (29). Matured and dried seeds were collected, and extraneous material was removed.…”
Section: Sample Collectionmentioning
confidence: 99%
“…Four hundred seventy-five accessions of cowpea consisting of indigenous and exotic collections were taken from MTS of National Gene Bank at ICAR-NBPGR, New Delhi, India, having high variability in seed morphology. Using Augmented Block Design accessions were grown in Issapur experimental farm, New Delhi, India, following standard agronomic practices (29). Matured and dried seeds were collected, and extraneous material was removed.…”
Section: Sample Collectionmentioning
confidence: 99%
“…The linear correlation between starch, amylose, total dietary fiber, protein, oil, phenols, and phytate was done using a Pearson correlation matrix and plotted using the Jamovi statistical package. The data was also subjected to PCA using Jamovi to identify superior traits responsible for the variation among them [ 35 ] .…”
Section: Methodsmentioning
confidence: 99%
“…Recently, in Europe the consumption of high protein vegetables, such as cowpea, is intensively promoted [ 10 ]. Cowpea is characterized by high seed protein content even higher than 30% [ 343 , 344 ] and low-fat content as well as a significant concentration of carbohydrates [ 3 , 345 ].…”
Section: Cowpea Plant Genetic Resources For Main Productivity Constra...mentioning
confidence: 99%
“…Padhi et al [ 345 ], evaluating 120 cowpea genotypes, found remarkable variability among them regarding their proximate composition. Proximate and nutrient composition of cowpea fresh pods and seeds have been found to be strongly affected by environment [ 15 ] and genotype [ 346 , 347 , 348 ], while a genotype x environment interaction is also usually present [ 10 , 174 , 349 ].…”
Section: Cowpea Plant Genetic Resources For Main Productivity Constra...mentioning
confidence: 99%
See 1 more Smart Citation